비만 청소년의 주관적 구강증상경험 관련 요인 - 박신영; Sin-young Park (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives: The purpose of this study is to identify the associated factors with subjective oral symptoms experience of obesity adolescents. Methods: The study subjects were targeting 8,139 obesity adolescents and 55,601 non-Obesity adolescents who completed 2016 Korean Youth Risk Behavior Web-based survey. Dependent variables were subjective oral symptoms experiences of fracture teeth, pain, throbbing pain, periodontal pain & bleeding, mucosal disease and bad breath. Independent variables were demographic characteristics of the subjects, oral health behaviors, health behaviors and eating habits. Results: Obesity adolescents were 12.8% with 61.9% subjective oral symptoms experience. Regarding the related factors of subjective oral symptoms experience of obesity adolescents, the factors were identified to be significantly higher in high school (OR=1.72) compared to middle school, learning achievement was higher in middle (OR=1.09) and lower (OR=1.31) compared to high, economic status was higher in lower (OR=1.09) compared to high, sealant experience (OR=1.10) and scaling experiences (OR=1.12) responded no were higher compared to responded yes, smoking experiences responded yes(OR=1.08) were higher compared to responded no, sweet drink (OR=1.14) and fastfood (OR=1.13) consumption were higher in consumption compared to non-consumption and females (OR=0.46) were higher than males. Oral symptoms experience were lower that father and mother's level of education were under high school graduation (OR=0.86) compared to unknown, economic status was in case of middle (OR=0.93) compared to high, tooth brushing was lower in under 1 time (OR=0.76), 2 times (OR=0.61) compared to more than 3 times, vigorous physical activities responded no (OR=0.75) were lower, compared to yes, vegetable consumption was lower in non-consumption (OR=0.68) compared to consumption. Conclusions: Subjective oral symptoms experiences were identified higher in obesity adolescents than non-obesity adolescents. It would be useful to use the results of this study to reduce oral symptoms and necessary to develop a program system considering characteristics of obesity adolescents.